Evaluasi Program Badan Usaha Milik Desa (Bumdes) Dalam Pengembangan Desa Wisata di Nagori Karang Anyar Kecamatan Gunung Maligas Kabupaten Simalungun - Ainul Latifah Br Simamora; Zoraya Alfathin Rangkuti (Public Inspiration : Jurnal Administrasi Publik, 2024)
The Village Owned Enterprises Program (BUMDES) is a form of program established by the Village Government to improve the village economy through developing the village’s potential. BUMDES ains to improve the village economy, increase community businesses in managing village economic potential. However, in practice it is still not targeted and there is no change in the independence of the people in the village. This research aims to determine and evaluate BUMDES in the Development of Tourism Villages in Nagori Karang Anyar.The resarch method used in this research is descriptive research with a qualitative approach. Data collection was carried out using interviews, observation, documentation, and literature techniques. Qualitative data analysis using the CIPP evaluation model theory approach (Context, Input, Process, Product) proposed by Daniel Stufflebeam (1993). The results of the research show that in the implementation of the BUMDES context evaluation there are still problems in developing business activities that are not yet optimal. However, judging from the target, it is in accordance with the provisions marked by improving infrastructure and developing types of business. Then, in the evaluation of inputs in its implementation was not transparent and did not understand the procedures for implementing BUMDES activities, causing the implementation to not receive a good response from the community. Then the process evaluation shows that program implementation is not in accordance with the implementation that is not in accordance with the implementation plan, indicated by business activities whose implementation is not optimal. And the product evaluation (results) shows that the presence of BUMDES in Nagori Karang Anyar in developing tourist villages is still not optimal in its implementation. In the Management of program implementation, there are still problems that cause the program to experience many obstacles, including the lack of Village Government supervision in the continuity of BUMDES in Nagori Karang Anyar.